GameMaker : Studio For Dummies. - Rohde, Michael (--For dummies., 2014)
Get gaming faster with the official guide to GameMaker: Studio GameMaker: Studio allows you to create your own games, even with zero coding experience, and GameMaker: Studio For Dummies is a complete guide to the ins and outs of the program. Create the game you've always wanted to play in record time and at a fraction of the cost of traditional game development methods. You'll have the flexibility to develop 2D games for Android, iOS, desktops, and the Web. Gain a professional perspective on this revolutionary path to game creation and publishing. Using GameMaker: Studio may.